Associação entre o tempo de tratamento e uso de suplementos nutricionais orais no consumo alimentar e frequência de inadequação dietética em pacientes com câncer de cabeça e pescoço - Ferreira, Isabela Borges (2019)
Background: Dietary intake of head and neck cancer (HNC) patients is affected by tumor site and symptoms arising from cancer treatment, increasing rates of malnutrition and mortality. Few studies investigate dietary intake and there is no evidence on frequency of energy and nutrients inadequacy in HNC patients. The aim of this study was to investigate the association of treatment moment and oral nutritional supplements (ONS) use on dietary intake and frequency of energy and nutrients inadequacy in HNC patients. Methods: A prospective study was perfomed in 65 patients with HNC from July 2017 to November 2018 in a university tertiary hospital in three moments: before or at beginning (T0), in the middle (T1 ~ four weeks) and immediately at the end of treatment (T2 ~ eight weeks). Dietary intake data were obtained from mean of three 24-Hour Dietary Recalls and prevalence of inadequacy was calculated by Estimated Average Requirement cut-off point method. Generalized Estimating Equations were used to determine the association of treatment moment and ONS on energy and nutrients intake and Generalized Linear Models were used to determine the association between ONS and Body Mass Index (BMI), adjusted for treatment, sex, age, tumor site and T stage. Results: Energy and macronutrients intake decreased in the middle (T0-T1) and then improves (T1-T2) at the end of treatment (p < 0.001 for both). Micronutrients intake increased over treatment, because ONS use, but still presented a high inadequacy intake probability, mainly for calcium, magnesium and vitamin B6, being almost 100% for those who did not use ONS. Patients using ONS more often had lower BMI. Conclusion: Treatment moment and ONS use were associated with dietary intake, so that energy and macronutrients intake decreased and micronutrients intake, due to ONS use, increased by approximately one month of treatment. Prevalence of inadequacy of energy and nutrients intake was high, even with ONS use. Therefore, we strongly recommend nutritional counseling should be initiated from diagnosis to optimize macronutrients adequacy in conjunction with ONS prophylactic prescription, to adjust micronutrients intake to prevent worse prognosis and nutritional status.